Gameplay Development of "Power Egg" As Interactive Learning Media of Arithmetic and Motoric Exercises for Elementary School Students - Wardhono, Wibisono S.; Arwani, I; Napitu, M.I.C.S. (INVOTEC, 2017)
Difficulties of learning mathematics, especially basic arithmetic like addition, subtraction, multiplication and division, most commonly found in children of elementary school. The material covering basic arithmetic addition, subtraction, multiplication and division began to be taught to children aged 6-9 years that is between grades 1st to 3rd of elementary school. The research’s goals are developing interesting gameplay and interactive games as media learning of arithmetic for elementary school students in grade 1st to 3rd. Development of gameplay is expected to increase the interest of elementary school students on the concept of arithmetic and it will have implications for the success of teaching and learning arithmetic concepts for students. "Power Egg" is an interactive educational game. The game is designed based on the needs of gameplay by adding motoric exercises with the utilization of Kinect VR technology as input media. The game users target was Elementary Schools Students grade 1st to 3rd. The results of game testing showed that all students enjoy the games and 96% of students want to try the game again. After playing this game, the evaluation results of arithmetic material tested to thirty elementary school students showed an increase up to 8.8% compared to the evaluation before the students run the game.